2021
DOI: 10.1111/tpj.15599
|View full text |Cite
|
Sign up to set email alerts
|

The small RNA‐mediated gene silencing machinery is required in Arabidopsis for stimulation of growth, systemic disease resistance, and suppression of the nitrile‐specifier gene NSP4 by Trichoderma atroviride

Abstract: Trichoderma atroviride is a root-colonizing fungus that confers multiple benefits to plants. In plants, small RNA (sRNA)-mediated gene silencing (sRNA-MGS) plays pivotal roles in growth, development, and pathogen attack. Here, we explored the role of core components of Arabidopsis thaliana sRNA-MGS pathways during its interaction with Trichoderma. Upon interaction with Trichoderma, sRNA-MGS-related genes paralleled the expression of Arabidopsis defense-related genes, linked to salicylic acid (SA) and jasmonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…Establishment of mutualistic associations between fungi and their host requires genetic and epigenetic reprogramming as well as metabolome modulation of both by the exchange of effector molecules [ 66 ]. Indeed, RdDM is essential in Arabidopsis to establish a beneficial relationship with the root-colonizing Trichoderma atroviride while DNA methylation and histone modifications are required for plant priming by the beneficial fungus against B. cinerea [ 67 ]. Importantly, it was just recently shown that during the mutualistic interaction of the ectomycorrhizal fungus Pisolithus microcarpus with Eucalyptus grandis , a fungal miRNA, Pmic_miR-8, targets the host NB-ARC domain containing transcripts in a cross-kingdom RNAi manner [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Establishment of mutualistic associations between fungi and their host requires genetic and epigenetic reprogramming as well as metabolome modulation of both by the exchange of effector molecules [ 66 ]. Indeed, RdDM is essential in Arabidopsis to establish a beneficial relationship with the root-colonizing Trichoderma atroviride while DNA methylation and histone modifications are required for plant priming by the beneficial fungus against B. cinerea [ 67 ]. Importantly, it was just recently shown that during the mutualistic interaction of the ectomycorrhizal fungus Pisolithus microcarpus with Eucalyptus grandis , a fungal miRNA, Pmic_miR-8, targets the host NB-ARC domain containing transcripts in a cross-kingdom RNAi manner [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Establishment of mutualistic associations between fungi and their host requires genetic and epigenetic reprogramming as well as metabolome modulation of both by the exchange of effector molecules (Kloppholz et al ., 2011). Indeed, RdDM is essential in Arabidopsis to establish a beneficial relationship with the root-colonizing Trichoderma atroviride while DNA methylation and histone modifications are required for plant priming by the beneficial fungus against B. cinerea (Rebolledo-Prudencio et al ., 2021). Importantly, it was just recently shown that during the mutualistic interaction of the ectomycorrhizal fungus Pisolithus microcarpus with Eucalyptus grandis , a fungal miRNA, Pmic_miR-8, targets the host NB-ARC domain containing transcripts in a cross-kingdom RNAi manner (Wong-Bajracharya et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…They provide a better defense mechanism against the aphid Macrosiphum euphorbiae and the moth Spodoptera littotalis in tomato plants [ 102 ], proving that T. atroviride may be able to control pathogens indirectly, modulating plant physiology. Besides modification of the transcription of genes involved in plant defense responses, colonization by T. atroviride also induces Arabidopsis ’s sRNA-mediated gene silencing, leading to an increase in gene expression of JA and SA-mediated pathways, which in turn induces priming and increases resistance in the plant against B. cinerea [ 103 ].…”
Section: Biocontrol Potential Of Registered Trichoderma ...mentioning
confidence: 99%